Kebijakan Perdagangan Uni Eropa terhadap Produk Logam Dasar - Nida Tsabitah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Trade relations between the European Union and China experienced rapid growth during the first two decades of the 21st century. The increase in trade relations is in line with the implementation of EU trade barriers through anti-dumping investigation reports at the World Trade Organization (WTO) against Chinese products. In the period 2001 – 2022, Chinese base metal products became the commodity with the most reported cases in antidumping investigations carried out by the EU at the WTO. However, in the same period, the value of imports of basic metal products to the European Union was lower compared to the value of imports of other products such as electricity & equipment as well as machine products, nuclear reactors and boilers. This article aims to explain the reasons behind the European Union's stance in making Chinese base metal products the most common commodity in antidumping investigation reports at the WTO. This article uses Alan Bryman's qualitative method, and the neoclassical realism theory proposed by Gideon Rose to analyze European Union policy towards Chinese Base Metal Products. The application of systemic pressure variables in neoclassical realism theory influences the European Union's position in the international system as an external factor, while there are other variables, in this case internal factors, which also influence the European Union's strategic trade policy-making process through the European Commission. The findings of this article show that China's dominance in world metals consumption and production since the early 2000s, especially in the 2013 – 2017 period, triggered the European Commission's perception that the European base metals industry was experiencing a decline in competitiveness and needed protection. In the 2013-2017 period, China's contribution to the world base metals market increased by 13% compared to 8% in the previous decade. On the other hand, the European Commission has maximized its influence in mobilizing national forces as outlined in the resolution document 2017/C399/12 to build a sustainable base metals industry. The European Union's trade policy in making Chinese base metal products the highest case report in antidumping investigations at the WTO over the last two decades, was driven by the European Commission, as the trade policy formulation unit in the European Union, to respond to systemic challenges in the global base metals market.